1991
DOI: 10.1111/j.1348-0421.1991.tb01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycolic Acid‐Containing Glycolipid as a Possible Virulence Factor of Rhodococcus equi for Mice

Abstract: By the use of various Rhodococcus equi strains differing in the length of carbon chains of glycolipid, we examined whether the glycolipid, glucose monomvcolate, was contributing to the virulence of R. equi for mice.R. equi strains with longer carbon chain mycolic acid showed a higher virulence as determined by lethality and granuloma formation in mice than those with shorter ones. When purified glycolipid was injected into mice, granuloma formation and liver damage were most prominent with the glycolipid havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…In a recent study, McNeil et al identified three distinct mycolic acid patterns among a collection of R. equi reference strains and clinical isolates; these patterns were also associated with differences in the antimicrobial susceptibility and colony morphology of these strains and isolates (380). In another study, Gotoh et al associated three different mycolic acid patterns of R equi isolates with their virulence in vivo in a mouse model (223). In this study, R equi isolates having longer carbon chains for mycolic acid-glycolipid showed a higher degree of virulence, as determined by lethality and granuloma formation in mice, than did those having shorter carbon chains (223).…”
Section: Pathogenicity Studiesmentioning
confidence: 68%
See 4 more Smart Citations
“…In a recent study, McNeil et al identified three distinct mycolic acid patterns among a collection of R. equi reference strains and clinical isolates; these patterns were also associated with differences in the antimicrobial susceptibility and colony morphology of these strains and isolates (380). In another study, Gotoh et al associated three different mycolic acid patterns of R equi isolates with their virulence in vivo in a mouse model (223). In this study, R equi isolates having longer carbon chains for mycolic acid-glycolipid showed a higher degree of virulence, as determined by lethality and granuloma formation in mice, than did those having shorter carbon chains (223).…”
Section: Pathogenicity Studiesmentioning
confidence: 68%
“…It is difficult to compare these three studies (89,223,380), since there were no common internal control strains in the study of Gotoh et al (223). It is apparent that mycolic acid patterns constitute useful phenotypic markers for the rhodococci; however, representative strains from all of the 13 validly described Rhodococcus spp.…”
Section: Laboratory Diagnosismentioning
confidence: 98%
See 3 more Smart Citations